DACA and the Supreme Court: How We Got to This Point, a Statistical Profile of Who Is Affected, and What the Future May Hold for DACA Beneficiaries. (December 2019) - Alulema, Daniela
Executive Summary: In June 2012, the Obama administration announced the establishment of the Deferred Action for Childhood Arrivals (DACA) program, which sought to provide work authorization and a temporary reprieve from deportation to eligible undocumented young immigrants who had arrived in the United States as minors. Hundreds of thousands of youth applied for the program, which required providing extensive evidence of identity, age, residence, education, and good moral character. The program allowed its recipients to pursue higher education, to access more and better job opportunities, and to deepen their social ties in the United States. This article provides a statistical portrait of DACA recipients based on administrative data from US Citizenship and Immigration Services (USCIS) and estimates drawn from the 2017 American Community Survey (ACS) Census data. It finds the following: As of September 30, 2019, there were 652, 880 active DACA recipients. Sixty-six percent of recipients are between the ages of 21 and 30. The top five countries of birth for DACA recipients are Mexico (80 percent), El Salvador (4 percent), Guatemala (3 percent), Honduras (2 percent), and Peru (1 percent). DACA recipients reside in all 50 states and Washington, DC, and in US territories including Puerto Rico, Guam, and the Virgin Islands. The top five states with the highest number of DACA recipients are California (29 percent), Texas (17 percent), Illinois (5 percent), New York (4 percent), and Florida (4 percent). Eighty-one percent of DACA recipients has lived in the United States for more than 15 years. Six percent is married to US citizens, 4 percent to lawful permanent residents (LPRs), and 13 percent to undocumented immigrants. Among US-born children younger than 18 years, 346, 455 have at least one DACA parent. Fifty-five percent of DACA recipients graduated from high school, 36 percent has some college education, and 7 percent a bachelor's degree or higher. Ninety-five percent is employed. The Trump administration rescinded the DACA program in September 2017, leaving recipients and their families in a legal limbo. Federal litigation led to a nationwide preliminary injunction and DACA's partial reinstatement for existing recipients. At this writing, the case is before the US Supreme Court, which will determine the program's fate. Beyond its statistical portrait, the article provides testimonies from DACA recipients who recount how the program improved their lives and their concerns over its possible termination. It also provides recommendations for Congress, local and state governments, and immigration advocates. In particular, it recommends passage of legislation that would create a path to citizenship for DACA recipients and programs and policies to support and empower young immigrants.